PEMANFAATAN APLIKASI POWTOON DALAM PEMBUATAN MEDIA PEMBELAJARAN BAGI GURU SMAN 4 KEPAHIANG - Andik Purwanto; Eko Risdianto; Desy Hanisa Putri; Fitri Masito; I Gusti Agung Ayu Mas Oka (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Penerbangan Palembang, 2021)
In this era of disruption, the world of education is required to be able to equip students with 21st Century Skills. Not only for students, teachers and lecturers must also be prepared to face these skills. Teachers and lecturers must have strong core competencies, have soft skills include: Critical Thinking, creativity, communication, and collaboration. To achieve 21st-century skills, learning trends and best practices must also be adjusted, one of which is by using an ICT-based learning model approach such as Learning Media in the form of Animated Videos created using the PowToon application. This activity aims to (1) describe the improvement of skills, especially digital literacy of teachers in making learning media using PowToon, so that later it can improve student understanding (2) increase teacher motivation in using Information Technology, especially using the PowToon application in helping to learn, especially for high school students 4 Kepahiang so that it can motivate teachers to use the latest learning innovations. Method Activities using RPA (Participatory Rural Appraisal) is an approach and method that allows the community to jointly analyze life problems to formulate real plans and policies. The form of this activity is in the form of training or workshops which are attended by 33 teachers of SMAN 4 Kepahiang. From the results of this service, almost all teachers who participated in this activity were enthusiastic and could absorb the material provided well. From the results of this service, almost all teachers who participated in this activity were enthusiastic and could absorb the material provided well. So it can be concluded that this training activity is running by the desired goals and can be followed up for the next service program.